Pembuatan Aplikasi Mobile "Wonderful of Minangkabau" sebagai Gudang Informasi Pariwisata di Sumatera Barat Melalui Website Kodular - Ronaldo Ronaldo; Ardoni Ardoni (Info Bibliotheca: Jurnal Perpustakaan dan Ilmu Informasi, 2020)
West Sumatra has unique traditions and culture and has become one of the attractions and destinations for both local and long-distance tourism. However, the lack of information and the lack of promotion carried out by the Government of West Sumatra has made the tourism sector run sluggishly, therefore a promotional tool that is capable of improving the tourism sector is needed. This paper reports the results and process of creating a tourism application called "Wonderful of Minangkabau". The research method used is descriptive research. Descriptive method is a method in examining the status of human groups, an object, a condition or a thought or tourism class in the present. The purpose of this descriptive research is to make descriptions, descriptions or paintings systematically, factually and accurately regarding facts, characteristics and relationships between phenomenon under investigation. This application is built using the Kodular website which is an application website that allows users to create applications based on the Android operating system using Block Programming so that users do not need to do coding (writing programming code). This application is expected to help tourists who want to get information about tourism in West Sumatra Province quickly and precisely.